Substituent effects in twisted dibenzotetracene derivatives: Blue emitting materials for organic light-emitting diodes. (January 2015) - Xiao, Jinchong; Liu, Zhenying; Zhang, Xuemin; Wu, Weichen; Ren, Tiejun; Lv, Bo; Jiang, Li; Wang, Xuefei; Chen, Hua; Su, Wenming; Zhao, Jianwen
Abstract: A series of dibenzotetracene derivatives containing different substituents at the 11-, 12-positions have been successfully synthesized and characterized. Single crystal X-ray analysis indicates that the new molecules have a twisted structure, which can effectively decrease the intermolecular aggregation in the solid-state. The effect of both substituent and packing on the corresponding physical properties was also investigated. In addition, organic light-emitting diodes doped with 11, 12-difluoro-9, 14-diphenyl-dibenzo[de, qr]tetracene into the emitter 9, 9′-(1, 3-phenylene)bis-9 H -carbazole were fabricated and exhibit good performance. Graphical abstract: Highlights: A series of dibenzotetracene derivatives were synthesized. Single crystal analysis shows these compounds have twisted structures. Electroluminescent devices were fabricated to assess the performance of the new dibenzotetracene.